2021
DOI: 10.1136/annrheumdis-2021-220647
|View full text |Cite|
|
Sign up to set email alerts
|

Immunogenicity and safety of the BNT162b2 mRNA COVID-19 vaccine in adult patients with autoimmune inflammatory rheumatic diseases and in the general population: a multicentre study

Abstract: IntroductionVaccination represents a cornerstone in mastering the COVID-19 pandemic. Data on immunogenicity and safety of messenger RNA (mRNA) vaccines in patients with autoimmune inflammatory rheumatic diseases (AIIRD) are limited.MethodsA multicentre observational study evaluated the immunogenicity and safety of the two-dose regimen BNT162b2 mRNA vaccine in adult patients with AIIRD (n=686) compared with the general population (n=121). Serum IgG antibody levels against SARS-CoV-2 spike S1/S2 proteins were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

84
787
12
22

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 575 publications
(905 citation statements)
references
References 48 publications
84
787
12
22
Order By: Relevance
“…Thus, our findings should be interpreted with caution and as hypothesis generating. Nevertheless, other groups have also reported that some patients with CID receiving immunosuppressants mounted reduced humoral responses compared with immunocompetent participants ( 18 , 19 , 29 ).…”
Section: Discussionmentioning
confidence: 98%
“…Thus, our findings should be interpreted with caution and as hypothesis generating. Nevertheless, other groups have also reported that some patients with CID receiving immunosuppressants mounted reduced humoral responses compared with immunocompetent participants ( 18 , 19 , 29 ).…”
Section: Discussionmentioning
confidence: 98%
“…The multi-compartment vaccine response induced by BNT162b2 may have important ramifications, particularly in immunocompromised populations. Reduced humoral responses have been reported to SARS-CoV-2 infection or BNT162b2 in patients with solid organ transplant (68)(69)(70), cancer (71), or immune-mediated inflammatory diseases (72,73). The identification of altered proteins or specific cell populations to serve as biomarkers for successful vaccination may provide important insight to monitor development and continued protection of these vulnerable populations.…”
Section: Immunization Withmentioning
confidence: 99%
“…Another limitation is the absence of a control group. However, Furer and colleagues 8 reported that the prevalence of mild adverse events was similar in patients with autoimmune rheumatic and musculoskeletal disease and controls.…”
mentioning
confidence: 96%